Out of Work Unemployment and Government in Twentieth-Century America - Vedder, Richard K (NYU Press, 1997)
Redefining the way we think about unemployment in America today, Out of Work offers devastating evidence that the major cause of high unemployment in the United States is the government itself. An Independent Institute Book